Rancang Bangun Nextcloud Storage Sebagai Media Penyimpanan Data E-Learning di SMA Negeri 2 Manokwari: Nextcloud Storage Design as E-Learning Data Storage Media in SMA Negeri 2 Manokwari - Irwan Moses Toto; Parma Hadi Rantelinggi; Marlinda Sanglise (JISTECH: Journal of Information Science and Technology, 2023)
Conventional learning systems in general have difficulty in distributing teaching materials which certainly require costs, giving assignments to students that burden the teacher himself in the collection of assignments and the process of assessing assignments, subject matter whose storage security in memory/flashdisk is not guaranteed so that with the nextcloud storage media which is cloud storage and integrated with e-learning applications, has features that are in accordance with the learning environment and easy to use both teachers and students. The system will be built using Moodle on hosting with Nextcloud as a storage medium, then using the SDLC method as a system design so that this system is well integrated. With this application, the needs of students and teachers in online teaching and learning activities are answered by using every feature in e-learning with Nextcloud helping the performance of the e-learning system application.